2019
DOI: 10.3847/2041-8213/ab1590
|View full text |Cite
|
Sign up to set email alerts
|

Pulsar Radio Emission Mechanism: Radio Nanoshots as a Low-frequency Afterglow of Relativistic Magnetic Reconnection

Abstract: In this Letter we propose that coherent radio emission of Crab, other young energetic pulsars, and millisecond pulsars is produced in the magnetospheric current sheet beyond the light cylinder. We carry out global and local two-dimensional kinetic plasma simulations of reconnection to illustrate the coherent emission mechanism. Reconnection in the current sheet beyond the light cylinder proceeds in the very efficient plasmoid-dominated regime, and current layer gets fragmented into a dynamic chain of plasmoids… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 30 publications
6
103
0
Order By: Relevance
“…Therefore, the reconnection process produces an emission with wavelength of the order of a few dozens of Larmor radii of particles within the sheet. The fms pulses are clearly observed in simulations of the reconnection in the current sheet [46]; it was found that they take away roughly 0.5% of the magnetic energy dissipated during the reconnection process.…”
Section: Radiation From Reconnecting Current Sheetsmentioning
confidence: 96%
“…Therefore, the reconnection process produces an emission with wavelength of the order of a few dozens of Larmor radii of particles within the sheet. The fms pulses are clearly observed in simulations of the reconnection in the current sheet [46]; it was found that they take away roughly 0.5% of the magnetic energy dissipated during the reconnection process.…”
Section: Radiation From Reconnecting Current Sheetsmentioning
confidence: 96%
“…The latest work also shows that in the reconnection region, radio waves may be emitted by coalescence of magnetic islands in the CS that produces magnetic perturbations propagating away [28,31,52]. For this process, the predicted spectral flux density of the radio waves with the frequency ν is…”
Section: E Implication To Observationmentioning
confidence: 99%
“…That the magnetospheric current sheet may be responsible for the observed radiation from rapidly rotating neutron stars has already been put forward in the literature but with an emphasis on the microscale structure of the sheet and magnetic reconnection (Uzdensky & Spitkovsky 2014; Philippov et al. 2019, and the references therein). According to the results obtained here, in contrast, it is the accelerated motion at a superluminal speed of the sharply localized macroscopic distribution pattern of this current sheet that underlies its candidacy as a possible source of the radiation received from such objects.…”
Section: Resultsmentioning
confidence: 99%